Reduced liver mitochondrial energy metabolism impairs food intake regulation following gastric preloads and fasting - Michael E. Ponte; John C. Prom; Mallory A. Newcomb; Annabelle B. Jordan; Lucas L. Comfort; Jiayin Hu; Patrycja Puchalska; Devin C. Koestler; Caroline E. Geisler; Matthew R. Hayes; E. Matthew Morris (Molecular Metabolism)
Objective: The capacity of the liver to serve as a peripheral sensor in the regulation of food intake has been debated for over half a century. The anatomical position and physiological roles of the liver suggest it is a prime candidate to serve as an interoceptive sensor of peripheral tissue and systemic energy state. Importantly, maintenance of liver ATP levels and within-meal food intake inhibition is impaired in human subjects with obesity and obese pre-clinical models. Previously, we have shown decreased hepatic mitochondrial energy metabolism (i.e., oxidative metabolism & ADP-dependent respiration) in male liver-specific, heterozygous PGC1a mice results in increased short-term diet-induced weight gain with increased within meal food intake. Herein, we tested the hypothesis that decreased liver mitochondrial energy metabolism impairs meal termination following nutrient oral pre-loads. Methods: Liver mitochondrial respiratory response to changes in ΔGATP and adenine nucleotide concentration following fasting were examined in male liver-specific, heterozygous PGC1a mice. Further, food intake and feeding behavior during basal conditions, following nutrient oral pre-loads, and following fasting were investigated. Results: We observed male liver-specific, heterozygous PGC1a mice have reduced mitochondrial response to changes in ΔGATP and tissue ATP following fasting. These impairments in liver energy state are associated with larger and longer meals during chow feeding, impaired dose-dependent food intake inhibition in response to mixed and individual nutrient oral pre-loads, and greater acute fasting-induced food intake. Conclusions: These data support previous work proposing liver-mediated food intake regulation through modulation of peripheral satiation signals.